Efr3a Insufficiency Attenuates the Degeneration of Spiral Ganglion Neurons after Hair Cell Loss - Hu, Haixia; Ye, Bin; Zhang, Le; Wang, Quan; Liu, Zhiwei; Ji, Suying; Liu, Qiuju; Lv, Jingrong; Ma, Yan; Xu, Ying; Wu, Hao; Huang, Fude; et al. (Frontiers in Molecular Neuroscience, 2017)
Sensorineural hearing loss (SNHL) is caused by an irreversible impairment of cochlear hair cells and subsequent progressive degeneration of spiral ganglion neurons (SGNs). Eighty-five requiring 3 (Efr3) is a plasma membrane protein conserved from yeast to human, and knockout of Efr3a was reported to facilitate the survival of hippocampal newborn neurons in adult mice. Previously, we found Efr3a expression in the auditory neural pathway is upregulated soon after the destruction of hair cells. Here we conducted a time-course analysis of drug-caused damage to hearing ability, hair cells and SGNs in Efr3a knocking down mice (Efr3a-/+, Efr3a KD) and their wild type littermates. Functional examination showed that both groups of mice suffered from serious hearing loss with a higher level of severity in WT mice. Morphologic observation following drugs administration showed that both WT and Efr3a KD mice went through progressive loss of hair cells and SGNs, in association with degenerative changes in the perikarya, intracellular organells, cell body conformation in SGNs, and the changes of SGNs in WT mice were more severe than in Efr3a KD mice. These beneficial effects of Efr3a KD could be ascribed to an increase in the expression of some neurotrophic factors and their receptors in Efr3a KD mice. Our results indicate that Efr3a insufficiency suppresses drug-caused SNHL neurodegeneration in association with an increase in the expression of some neurotrophic factors and their receptors, which may be targeted in the treatment of neurodegeneration.